Global status of neglected human Linguatula infection: a systematic review of published case reports - Tabaripour, Rabeeh; Keighobadi, Masoud; Sharifpour, Ali; Azadeh, Hossein; Shokri, Azar; Banimostafavi, Elham Sadat; Fakhar, Mahdi; Abedi, Soodeh (Parasitology research (1987), 2021)
Human linguatulosis is a rare but highly specialized pentastomid parasitic infection all around the world. The disease is caused by worm-like parasites which share some morphologic features of arthropods and annelids. The life cycle of Linguatula spp. is provided as an example of pentastomid biology. The adult forms of Linguatula spp. are found in the nasal passages and frontal sinuses of dogs and other canids, domestic animals, and humans. Infestation may occur in the viscera, where immature forms develop in the liver, spleen, lungs, eyes, and other organs, or in the nasopharyngeal area. This review includes previous studies on the genus Linguatula in Iran and other countries from 1940 to 2019. Considering a few reports of human infestation, a comprehensive search was performed on both English and Persian databases for publications reporting human cases all around the world. Finally, 30 papers of 62 human cases were included in this study. The mean age of the patients was 25.8 years (varied from 8 to 79 years). Altogether, 41 (66.1%) and 21 (33.9%) of the patients were female and male respectively. The maximum cases ( n = 25) were from Sudan. Nasopharynx was the most frequently involved organ in human cases. Our findings offer that physicians should consider the Linguatula infection in patients with complaints like unexpected dysphagia, with coughing, sneezing, and vomiting, after consuming raw/undercooked contaminated ruminant’s viscera.